Goethite Reduction by a Neutrophilic Member of the Alphaproteobacterial Genus Telmatospirillum - Gagen, Emma J.; Zaugg, Julian; Tyson, Gene W.; Southam, Gordon (Frontiers in Microbiology, 2019)
In tropical iron ore regions, biologically-mediated reduction of crystalline iron oxides drives ongoing iron cycling that contributes to the stability of surface duricrusts. This represents a biotechnological opportunity with respect to post-mining rehabilitation attempts, requiring re-formation of these duricrusts. However, cultivated dissimilatory iron reducing bacteria typically reduce crystalline iron oxides quite poorly. A glucose-fermenting microbial consortium capable of reducing at least 27 mmol/L goethite was enriched from an iron duricrust region. Metagenome analysis led to the recovery of a metagenome assembled genome (MAG) of an iron reducer belonging to the alphaproteobacterial genus Telmatospirillum. This is the first report of iron reduction within the Telmatospirillum and the first reported genome of an iron-reducing, neutrophilic member of the Alphaproteobacteria. The Telmatospirillum MAG encodes putative metal transfer reductases (MtrA, MtrB) and a novel, multi-heme outer membrane cytochrome for extracellular electron transfer. In the presence of goethite, short chain fatty acid production shifted significantly in favour of acetate rather than propionate, indicating goethite is a hydrogen sink in the culture. Therefore, the presence of fermentative bacteria likely promotes iron reduction via hydrogen production. Stimulating microbial fermentation has potential to drive reduction of crystalline iron oxides, the rate limiting step for iron duricrust re-formation.